Implementing Participatory Action Research in the Canadian North: A Case Study of the Gwich’in Language and Cultural Project - Ryan, Joan; Robinson, Michael P. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1990)
The Gwich’in Language and Cultural Project began in 1987 as a joint venture among the Teetl’it Gwich’in Band of Fort McPherson, Northwest Territories, the Arctic Institute of North America of the University of Calgary and the Ministry of Education of the Government of the Northwest Territories. From its inception the project utilized participatory action research methodology, augmented by the group dynamic process and a feminist approach to organization and coordination. This paper provides a case study evaluation of the Gwich’in Language and Cultural Project in the context of participatory action research and focuses on the discrete steps taken in the project’s development. The conclusions affirm the existing global participatory action research literature and extend the models originally developed by Tax (1988) and Hall (1988) to include the two new dimensions of group dynamics and a feminist perspective. The authors hope that other communities and action anthropologists will seek to replicate their methodology and that practitioners will also contribute to the evolving case study literature.